Dihydronaphthalenones from the endophytic fungus Botryosphaeria sp. BCC 8200 - Masahiko Isaka (2018)
Five new dihydronaphthalenones (1, 2a/2b, 3a/3b), four of which were isolated as two inseparable mixtures of isomers, together with two known compounds, 7-hydroxy-2-(2-hydroxypropyl)-5-methylchromone (4) and siderin (5), were identified as secondary metabolites of the endophytic fungus Botryosphaeria sp. BCC 8200. The structures were elucidated by interpretation of NMR spectroscopic and mass spectrometry data. Compounds 2a/2b, 3a/3b, and 5 exhibited weak cytotoxic activities against cancer cell lines. © 2009 Phytochemical Society of Europe.